Obstructive heart defects associated with candidate genes, maternal obesity, and folic acid supplementation. (2nd April 2015) - Tang, Xinyu; Cleves, Mario A.; Nick, Todd G.; Li, Ming; MacLeod, Stewart L.; Erickson, Stephen W.; Li, Jingyun; Shaw, Gary M.; Mosley, Bridget S.; Hobbs, Charlotte A.; ,
Abstract : Right‐sided and left‐sided obstructive heart defects (OHDs) are subtypes of congenital heart defects, in which the heart valves, arteries, or veins are abnormally narrow or blocked. Previous studies have suggested that the development of OHDs involved a complex interplay between genetic variants and maternal factors. Using the data from 569 OHD case families and 1, 644 control families enrolled in the National Birth Defects Prevention Study (NBDPS) between 1997 and 2008, we conducted an analysis to investigate the genetic effects of 877 single nucleotide polymorphisms (SNPs) in 60 candidate genes for association with the risk of OHDs, and their interactions with maternal use of folic acid supplements, and pre‐pregnancy obesity. Applying log‐linear models based on the hybrid design, we identified a SNP in methylenetetrahydrofolate reductase ( MTHFR ) gene (C677T polymorphism) with a main genetic effect on the occurrence of OHDs. In addition, multiple SNPs in betaine‐homocysteine methyltransferase ( BHMT and BHMT2 ) were also identified to be associated with the occurrence of OHDs through significant main infant genetic effects and interaction effects with maternal use of folic acid supplements. We also identified multiple SNPs in glutamate‐cysteine ligase, catalytic subunit ( GCLC ) and DNA (cytosine‐5‐)‐methyltransferase 3 beta ( DNMT3B ) that were associated with elevated risk of OHDs among obese women. Our findings suggested that the risk of OHDs was closely related to a combined effect of variations in genes in the folate, homocysteine, or glutathione/transsulfuration pathways, maternal use of folic acid supplements and pre‐pregnancy obesity. © 2015 Wiley Periodicals, Inc.